2006
DOI: 10.4028/www.scientific.net/msf.505-507.1207
|View full text |Cite
|
Sign up to set email alerts
|

Study of Hole-Machining on Pyrex Wafer by Electrochemical Discharge Machining (ECDM)

Abstract: The gap control problem in hole-machining of Pyrex® wafer by electrochemical discharge machining (ECDM) to obtain a smooth quality and acceptable material removal rate is studied. Analysis of the pulse signals shows that the average current pulse interval is constant, and it is mainly related to the ion translation conditions, such as the electrolyte concentration and the flushing strategy. The most steady and intense average current density can be obtained if the voltage on-time is around 3 times the average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…In voltages less than 28 V which results in a different electrochemical discharge regime, perfect edge and surface quality are obtained even at tool speeds less than 5 µm s −1 . This effect has also been reported for micro-hole drilling by gravity feed [7] and constant feed [16].…”
Section: Proposal Of a Model For Quality Micro-channels As A Function...supporting
confidence: 76%
“…In voltages less than 28 V which results in a different electrochemical discharge regime, perfect edge and surface quality are obtained even at tool speeds less than 5 µm s −1 . This effect has also been reported for micro-hole drilling by gravity feed [7] and constant feed [16].…”
Section: Proposal Of a Model For Quality Micro-channels As A Function...supporting
confidence: 76%
“…Some pioneering work about the material removal rate was done by Cook et al [8] and completed later by other research groups [9][10][11][12][13][14][15]. In [16], it was mentioned that micro-holes with a depth of 450 µm in glass are drilled typically in 30 s. Liao et al [17] reported that the maximal allowable feeding rate in hole-drilling at constant feed is typically around 15 µm s −1 . Characterization of the micro-hole quality and achieved geometrical tolerances has so far never been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, how to reduce HAZ and improve the microhole quality is a key question for widening ECDM applications. Liao and Peng [15] also reached this finding and used the stable spark condition to drill holes with diameter φ2 mm by adjusting the feeding rate and applying voltage. The smallest average taper angle is around 8 • .…”
Section: Introductionmentioning
confidence: 74%